Philosophical enquiry and autism: story/ing/ied bags of unexpected human and more-than-human encounters in speech-language therapy and classroom spaces - Babamia, Sumaya (School of Education, 2025)
This study is located within early childhood education, early childhood intervention and childhood dis/ability studies. The aim of the thesis is to explore the concept of ontoepistemic injustice for autistic children with/in educational and therapeutic settings. Current pedagogies and interventions are embedded in human-centric ontologies that position autistic child as lacking, immature, and often incapacitated epistemologically. Drawing on critical posthumanism, notably Karen Barad's Agential Realism, the study asks: how might the community of philosophical enquiry be put to work with children who present with significant challenges to enquiry-based learning? How can subjectivity for autistic children be re-configured outside of humanist narratives of mastery, skill and performance? The research questions were explored through postqualitative storying practices where communities of autistic learners participated in a teaching and learning approach known as Philosophy for/with Children. The philosophical enquiries took place at two learning centres in Johannesburg, South Africa. These centres were ‘outlier' educational facilities that accommodated the learning differences of children who were deemed to be intellectually in/eligible for mainstream or remedial schooling. Despite learning, language and communication dis/abilities, the enquiries produced philosophical thinking that emerged in unexpected spaces and times. Often, the thinking that emerged worked outside of language and voice yet were weighty and imbued with intensity as well as affect. The postqualitative analysis in the thesis disrupts the nature/culture binary which has historically positioned autistic child as being of dis/ordered mind. Diffractive engagement with the co-created data of videotapes, photographs, drawings, and fieldnotes troubled normative theories of child development in early childhood education and early intervention that still rely heavily on language and cognition. Of significance in this study is the re-configuration of child subjectivity ‘outside' of the adult human-centred privileges of language, power and agency. Postqualitative research methods highlighted the agency of the material-discursive and troubled the ontoepistemic status of autistic child as ‘lacking' and ‘less-than'. The study shows how Philosophy for/with Children, when theorised as a posthumanist transdisciplinary theorypractice of deep, attentive listening to children's questions and ideas, contributes to and innovates within the fields of autism studies, early childhood education and early intervention.